2017
DOI: 10.1016/j.foodchem.2016.09.130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and NaCl on the formation of 3-MCPD esters and glycidyl esters in refined, bleached and deodorized palm olein during deep-fat frying of potato chips

Abstract: The effects of frying duration, frying temperature and concentration of sodium chloride on the formation of 3-monochloropropane-1,2-diol (3-MCPD) esters and glycidyl esters (GEs) of refined, bleached and deodorized (RBD) palm olein during deep-fat frying (at 160°C and 180°C) of potato chips (0%, 1%, 3% and 5% NaCl) for 100min/d for five consecutive days in eight systems were compared in this study. All oil samples collected after each frying cycle were analyzed for 3-MCPD esters, GEs, free fatty acid (FFA) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 9 publications
4
48
0
1
Order By: Relevance
“…Several studies were published concerning the effect of NaCl on the formation of MCPD‐E and G‐E in foods . Wong et al showed an increase of both, 3‐MCPD‐E and G‐E contents during the deep‐frying of potato crisps (160–180 °C) with increasing NaCl content (0–5%). After five days frying‐life of the oil the 3‐MCPD‐E content in potato crisps with 5% NaCl was 2.5 times higher than in products without NaCl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies were published concerning the effect of NaCl on the formation of MCPD‐E and G‐E in foods . Wong et al showed an increase of both, 3‐MCPD‐E and G‐E contents during the deep‐frying of potato crisps (160–180 °C) with increasing NaCl content (0–5%). After five days frying‐life of the oil the 3‐MCPD‐E content in potato crisps with 5% NaCl was 2.5 times higher than in products without NaCl.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the simultaneous presence of NaCl (in wet breadings and marinades) and deep‐frying oil, both deep‐frying and pasteurization may be predestined processing steps leading to the formation of MCPD‐E and G‐E. Several studies were published regarding to the formation of MCPD‐E and G‐E in deep‐fried food . Deep‐frying temperature and time as well as the NaCl content in the deep‐fried products were investigated with respect to their effect on the formation of MCPD‐E and G‐E .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It causes various toxicological effects in kidney, in blood and induces tumors at long‐term exposure . Moreover, 3‐MCPD esters production is increased with an increase in NaCl concentration and frying temperature, conversely, it is decreased with an increase in frying duration …”
Section: Problems Of Potato Chips Industrymentioning
confidence: 99%
“…Our previous study indicated that the natural beef flavor production process has more favorable conditions to generate 3‐MCPD esters, as compared to the deodorization of refined oils . Similar to the flavor formation, the formation of 3‐MCPD esters was found to be dependent on the reaction temperature and time . The pH of Maillard reaction system may decrease to around 5.0–5.5 during the thermal process, promoting the formation of 3‐MCPD esters …”
Section: Introductionmentioning
confidence: 99%